(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The study was carried out at University Research Farm of the Department of Animal Science, Kano University of Science and Technology, Wudil, to investigate the effect of substituting Lasota vaccine (NCDV) with Garrafuni on eggs laying performance and blood metabolites of Loman brown hen. The birds were randomly allotted into four treatment in a completely randomized design with one hundred and twenty five (125) chicks per treatment. Treatment 1 was given lasota vaccine (NCDV) at first, third, seven and seventeen weeks respectively. Treatment 2 was given Garafuni 0.5g per litre for six days in the week whereas Treatment 3, 1.0g per litre and Treatment 4, 1.5g per litre of Garafuni for four and two days in the week respectively. At the end of the study, blood samples were collected from ten birds from each treatment for hematological and blood chemistry. The result shows that, the median laying pause days (38 days) in birds treated with 1.5 g Garahuni. Highest value (12.23g/dl) for haemoglobins was recorded in birds under 0g while birds under 1.0g (T3) had the lowest mean (10.76g/dl). The result of blood chemistry indicated that highest value (6.04 mmol/L) for urea was recorded among the birds under 0g while birds under 1.0g had the lowest mean (4.82 mmol/L). There were significant (P < 0.01) differences among the treatment means in total protein. It was concluded that Garahuni could substitute lasota vaccine and can be used via drinking water up to 1.0g per litre for four days without any deleterious